ALBUQUERQUE JR, Durval Muniz de. A invenção do Nordeste e outras artes. 4ª ed. Recife: FJN; Ed. Massangana; São Paulo: Cortez, 2009. 340 p. - Martinello, André Souza (Revista Territórios e Fronteiras, 2011)
Resenha.